THE ROLE OF PUBLIC SERVICE ETHICS IN IMPROVING GOOD GOVERNANCE IN GENERAL ELECTIONS IN INDONESIA - Zainul Djumadin (INFOKUM, 2022)
Good governance is the main focus of sustainable development in various countries, with the principles of transparency, accountability and obedience to the law. Public service ethics, as moral values related to the public interest, play a crucial role in directing the behavior and decisions of actors regarding the General Election. This research aims to explore the important role of public ethics in realizing good governance. This research method includes literature analysis, case studies, and interviews with stakeholders related to good governance. The results of this research show that the role of public service ethics is very important in improving good governance in holding general elections in Indonesia. Public service ethics provide a moral foundation for election administrators to carry out their duties with integrity, transparency and openness. In the context of accountability, public service ethics is the basis for being responsible for every action and decision taken during the general election process. Compliance with the law, as part of public service ethics, has also proven important in maintaining the integrity and fairness of the entire process.